Ebook usage at Curtin University Library: patterns, projections and strategy - Wells, David; Dumbell, Petra (VALA, 2010)
Since Curtin University Library began to collect ebooks in the early 2000s, we have used a variety of collection development and access models for different purposes. To a large extent different acquisition models have been aligned to different collection development goals. For example, acquisition of publishers' collection sets has been directed to providing long-term infrastructure for researchers; purchase of individual ebooks has been intended primarily to address short-term demand for materials required to support teaching and learning. This paper will examine the patterns of usage of different categories of ebooks to establish the extent to which method or philosophy of acquisition has an impact on ebook usage.